Dietary patterns and association with Iron deficiency among children and adolescents aged 9–17 years in rural Guangzhou, China: a cross-sectional study - Fu, Jinhan; Zeng, Chunzi; Huang, Jie; Guo, Jiaying; Su, Zheng; Luo, Shiyun; Zhang, Weiwei; Zhang, Zhoubin; Zhu, Huilian; Li, Yan (Frontiers in Nutrition, 2024)
Background: Iron deficiency and iron deficiency anemia cause a huge disease burden worldwide. Diet is an important factor affecting the iron levels. This study aims to explore the dietary patterns of school-aged children in rural areas of Guangzhou and their association with iron deficiency.: Data on dietary surveys, lifestyle, demographic and laboratory tests were gathered from rural school-age children in Guangzhou. Factor analysis was applied to derive dietary patterns. Robust Poisson regression and subgroup analysis were used to analyze the association between dietary patterns and iron deficiency. Results: A total of 2530 children and adolescents aged 9-17 years were enrolled. The prevalence of iron deficiency was 13.36%. Four dietary patterns were identified including snack & fast-food pattern, fruit & vegetable pattern, cereal & tuber pattern and meat & offal pattern. Both children and adolescents in the Q4 group (the highest propensity) of snack & fast-food pattern and cereal & tuber pattern had a higher risk of iron deficiency than the Q1 group (the lowest propensity). Both children and adolescents in the Q4 group of meat & offal pattern and fruit & vegetable pattern had a lower risk of iron deficiency than the Q1 group. The results of stratified analysis showed the negative effect of snack & fast-food pattern and the protective benefits of meat & offal pattern are more obvious for boys, and the negative effect of cereal & tuber pattern were obvious for girls. The negative effect or protective benefits of the four dietary patterns were obvious for children aged 9-13. Conclusions: Females, older children, and those with shorter sleep duration are at higher risk of iron deficiency. Snack & fast-food pattern and cereal & tuber pattern are risk factors for iron deficiency, and fruit & vegetable pattern and meat & offal pattern are protective factors for iron deficiency. The impact of diet on body iron levels is more obvious in boys and younger children. The findings of this study can provide evidence for formulating prevention and control measures on children and adolescents iron deficiency and iron deficiency anemia.